2018
DOI: 10.2147/copd.s152971
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific cardiopulmonary exercise testing indices to estimate the severity of inoperable chronic thromboembolic pulmonary hypertension

Abstract: BackgroundSex differences in chronic thromboembolic pulmonary hypertension (CTEPH) have been revealed in few studies. Although right heart catheterization (RHC) is the gold standard for clinical diagnosis and assessment of prognosis in pulmonary hypertension (PH), cardiopulmonary exercise testing (CPET) has been a more widely used assessment of functional capacity, disease severity, prognosis, and treatment response in PH. We hypothesized that the “sex-specific” CPET indices could estimate the severity of inop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, it is uncertain whether this survival difference is due to differences in comorbidity burden (Barco et al, 2020 ). Studies of a Chinese CTEPH cohort (Chen et al, 2018 ) and the Spanish Registry of Pulmonary Arterial Hypertension, which includes CTEPH patients (Escribano-Subias et al, 2012 ) also show improved survival in females (male HR 1.38, 95% CI: 1.03–1.83 ; p = 0.03) (Escribano-Subias et al, 2012 ). In a Japanese cohort of CTEPH patients, females have significantly higher cardiac index (2.7 ± 0.6 vs. 2.4 ± 0.7 L·min −1 ·m −2 ; p = 0.01) and lower right atrial pressure (4 ± 4 vs. 7 ± 6 mmHg; p = 0.0002) compared to males despite no difference in pulmonary vascular resistance (Shigeta et al, 2008 ).…”
Section: Divergent Rv Function Between Sexes In Cteph (Group 4 Ph)mentioning
confidence: 99%
“…However, it is uncertain whether this survival difference is due to differences in comorbidity burden (Barco et al, 2020 ). Studies of a Chinese CTEPH cohort (Chen et al, 2018 ) and the Spanish Registry of Pulmonary Arterial Hypertension, which includes CTEPH patients (Escribano-Subias et al, 2012 ) also show improved survival in females (male HR 1.38, 95% CI: 1.03–1.83 ; p = 0.03) (Escribano-Subias et al, 2012 ). In a Japanese cohort of CTEPH patients, females have significantly higher cardiac index (2.7 ± 0.6 vs. 2.4 ± 0.7 L·min −1 ·m −2 ; p = 0.01) and lower right atrial pressure (4 ± 4 vs. 7 ± 6 mmHg; p = 0.0002) compared to males despite no difference in pulmonary vascular resistance (Shigeta et al, 2008 ).…”
Section: Divergent Rv Function Between Sexes In Cteph (Group 4 Ph)mentioning
confidence: 99%
“…Also in humans, endothelial dysfunction is often present both in patients with acute pulmonary embolism, as well as with CTEPH, and correlates with disease severity (Reesink et al 2006;In et al 2016;Chibana et al 2017). In humans, CTEPH prevalence is higher in females (Kirson et al 2011), although male patients typically have a worse prognosis (Chen et al 2018). In the present study, male and female swine were used because we have previously shown that there are subtle differences in regulation of pulmonary vascular tone (de Beer et al 2010;de Wijs-Meijler et al 2017) and hence it is possible that sex also affects development of CTEPH and subsequent RV remodelling in our animals.…”
Section: Animal Modelmentioning
confidence: 99%
“…In an observational study aimed to estimate the incidence of risk factors of CTEPH in a cohort with first venous thromboembolism (N 23,329 patients), female sex was significantly associated with the development of the disease (Martinez et al, 2018). However, studies carried out in Spanish and Chinese cohorts have showed a better survival in women as compared with their male counterparts (Escribano-Subias et al, 2012;Chen et al, 2018). This improved survival could be related to better cardiac performance, with lower atrial pressure and higher cardiac index to similar PVR compared to men (Shigeta et al, 2008).…”
Section: Pulmonary Hypertension Groupmentioning
confidence: 99%